AliExpress's Internationalization: Strategies and Practices on Cross-Border E-Commerce Platforms - Chen, Zeying (Simen Owen Academic Proceedings Series, 2026)
This study conducts an in-depth examination of AliExpress's globalization strategies on cross-border e-commerce platforms, highlighting how the integration of "multi-tier ecological empowerment" and "glocalization" strategies fosters systemic innovation across five critical dimensions: market selection, platform operations, product assortment and pricing, logistics and payment, and marketing promotion. The findings indicate that AliExpress adopts a "mature-emerging" dual-track model for global market expansion: leveraging overseas warehouses and localized services to enhance timeliness in European and American markets, while deploying strategies such as "cross-border express delivery" to penetrate emerging markets including Southeast Asia. In addition, the company has developed a four-dimensional operational matrix, "POP self-operation + full hosting + semi-hosting + overseas hosting", to empower diverse types of sellers. Supported by data scraping and flexible testing mechanisms, the full-hosting model has increased the blockbuster success rate to 67%. By constructing six million square meters of overseas warehouses and implementing blockchain-based settlement technologies, AliExpress has optimized logistics and payment experiences. Moreover, the platform harnesses social media channels such as TikTok to achieve viral marketing at scale. These strategies have positioned AliExpress among the global top three in personalized shopping experience in PYMNTS rankings, while its share of organic traffic has risen to 63%. The paper also underscores the challenges AliExpress faces, including compliance risks, insufficient localization depth, and ESG-related pressures, and proposes targeted optimization measures. Overall, the research not only offers a replicable pathway for the globalization of Chinese manufacturing but also provides important insights for the future evolution of the cross-border e-commerce industry.